Optimization of secondary air system for enhanced combustion efficiency and CO2 emission reduction in 1000MW boilers - Tianlong Wang; Chaoyang Wang; Huibo Yan; Zhiqiang Liu; Shuai Ma (Results in Engineering, 2025)
The optimization of combustion processes in large-scale power generation systems is crucial for improving energy efficiency and reducing carbon dioxide (CO2) emissions.This study focuses on enhancing the combustion state in a 1000MW double tangential circular boiler by optimizing the secondary air system through a combination of CFD simulation and experimental verification. The original design of the secondary air ducts led to significant imbalances in air volume and pressure, resulting in issues such as furnace wall overheating and inefficient combustion. To address these challenges, a CFD model was established to analyze the flow field characteristics of the secondary air system, identifying the key areas where airflow imbalances occurred. The flow field of the secondary bellows on the front and rear walls was optimized by introducing a certain number of orifice plates and curved arc deflectors, and the effectiveness of this design was verified through thermal performance tests of the secondary air system. The results demonstrated that air flow deviations between front and rear walls were reduced from 45 % to 4 %, and pressure deviations decreased from 142 Pa to 5 Pa, significantly improving combustion uniformity, leading to more uniform combustion and improved boiler efficiency. This optimization not only enhances the operational efficiency of the boiler but also contributes to lower CO2 emissions, aligning with the goals of sustainable energy production. The findings provide valuable insights for future design improvements in power generation systems aimed at achieving greater sustainability and environmental compliance.